Comprehensive separation and identification of chemical constituents from Abelmoschus manihot (L.) medic by polyamide chromatography coupled with high‐performance counter‐current chromatography and preparative liquid chromatography. Issue 4 (26th August 2020) - Fan, Chen; Li, Nai; Cao, Xueli
Abstract: Three methods (polyamide chromatography coupled with high‐performance counter‐current chromatography (HPCCC) and preparative liquid chromatography) were used to detection and separation of flavonoids from Abelmoschus manihot (L.) Medic. For HPLC analysis, there are main six substances in Abelmoschus manihot (L.) Medic. After polyamide chromatography, the main flavonoids existed in fractions eluted between 50 and 90 % aqueous ethanol. Among these, four fractions of interest from column were separated by HPCCC with the different solvent system. And other two fractions were separated by preparative liquid chromatography. Six high‐purity flavonoids were obtained eventually and identified by MS, 1 H and 13 C NMR: rutin (1 ), hyperoside (2 ), isoquercitrin (3 ), avicularin (4 ), quercetin (5 ), amentoflavone (6 ). In addition, the substances 4 and 6 for the first time were isolated from Abelmoschus manihot (L.) Medic by HPCCC.